1994
DOI: 10.1111/j.1467-9450.1994.tb00956.x
|View full text |Cite
|
Sign up to set email alerts
|

The total workload of male and female white collar workers as related to age, occupational level, and number of children

Abstract: A questionnaire assessing various aspects of paid as well as unpaid forms of productive activity was mailed to stratified samples of male and female white collar workers, approximately matched for educational and occupational level. Data from 501 men and 679 women employed full time revealed traditional gender differences in terms of main responsibility for household duties, child care etc. In keeping with this, women reported higher levels of work overload, stress and conflict than men, which increased signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
154
0
17

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(182 citation statements)
references
References 16 publications
11
154
0
17
Order By: Relevance
“…In the present study household tasks are given the status of housework/unpaid work because of the assumption that work corresponds to any activity necessary for the maintenance of society (Waissmann, 2003). Our view is shared by other authors who consider both professional and domestic load in the analysis of females' health Bjorksten et al, 2001;Brisson et al, 1999;Krantz et al, 2005;Lundberg et al, 1994). In the context of those studies, our results are partly in accordance with those obtained using a white-collar sample by Krantz et al (2005) The authors found an interaction between work conditions and household only for female's health, while males responded more selectively to professional work hours.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study household tasks are given the status of housework/unpaid work because of the assumption that work corresponds to any activity necessary for the maintenance of society (Waissmann, 2003). Our view is shared by other authors who consider both professional and domestic load in the analysis of females' health Bjorksten et al, 2001;Brisson et al, 1999;Krantz et al, 2005;Lundberg et al, 1994). In the context of those studies, our results are partly in accordance with those obtained using a white-collar sample by Krantz et al (2005) The authors found an interaction between work conditions and household only for female's health, while males responded more selectively to professional work hours.…”
Section: Discussionsupporting
confidence: 91%
“…Men's low recovery level is surprising at first glance. Because women face a greater total workload than men (Lundberg, Marberg, & Frankenhaeuser, 1994), one would expect that women have less time and opportunities to recover after work. However, it seems that the picture is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…This inverse association was not replicated in a study of cardiovascular events among Japanese women (46), but, because only two cardiovascular events were recorded in the high-strain group, that finding remains open to chance. The stress of unpaid work at home (eg, child care) may be particularly important for women because they still carry a larger share of the responsibility for doing domestic duties (50,51). For example, findings from the Whitehall II study suggest that low control at home predicts CHD among women but not among men (52), and a Swedish study showed that a combination of stressful conditions at work and at home predicted perceived symptoms among women, whereas, for men, symptoms were more strongly determined by work stress alone (53).…”
Section: Discussionmentioning
confidence: 99%